2007
DOI: 10.1002/art.23158
|View full text |Cite
|
Sign up to set email alerts
|

Association of microsomal prostaglandin E synthase 1 deficiency with impaired fracture healing, but not with bone loss or osteoarthritis, in mouse models of skeletal disorders

Abstract: Objective. Prostaglandin E synthase (PGES) functions as the terminal enzyme in the biosynthesis of prostaglandin E 2 (PGE 2 ) and is a potent regulator of bone and cartilage metabolism. Among the 3 isozymes of PGES, microsomal PGES-1 (mPGES-1) is known to play the most critical role in the production of PGE 2 in pathophysiologic events. This study investigated the roles of mPGES-1 under normal physiologic and pathophysiologic conditions in the skeletons of mPGES-1-deficient (mPGES-1 ؊/؊ ) mice. Methods. Skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Therefore, the overexpression of TIMP-3 observed in mPGES-1 null mice could represent a protection against cartilage degradation in arthritis. It may explain, at least in part, the persistance of cartilage degradation in surgically induced OA in mPGES-1 null mice (45).…”
Section: Figurementioning
confidence: 99%
“…Therefore, the overexpression of TIMP-3 observed in mPGES-1 null mice could represent a protection against cartilage degradation in arthritis. It may explain, at least in part, the persistance of cartilage degradation in surgically induced OA in mPGES-1 null mice (45).…”
Section: Figurementioning
confidence: 99%
“…Although some studies have reported that mice lacking mPGES-1 do not show significant differences with respect to wild type animals in OA induced by surgical procedures [11], it is interesting to note that mPGES-1 defficiency results in milder arthritis and lower cartilage degradation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic ablation of mPGES-1 in mice has no apparent effects on normal skeletal development but causes a significant impairment in tibial fracture healing. 23 Tibial fractures in 5 of 10 mPGES-1-null mice failed to heal after 21 days, whereas 10 of 10 fractures healed in control mice. Levels of mPGES-1 mRNA peaked at 7 days after fracture in the mouse tibiae, which correlates with the peak period of callus cartilage formation.…”
Section: Prostaglandin Synthasesmentioning
confidence: 99%